Utilizing Digital Technology in Physical Education: A Review of the Latest Methods and Platforms - Muh Ilham Aksir (Journal Physical Health Recreation (JPHR), 2025)
The digital transformation of physical education has created a new paradigm of learning that is interactive, adaptive, and data-driven. This study aims to review recent methods and digital platforms applied in sports education by analyzing national and international research published between 2020 and 2025. A descriptive–analytical approach was employed by synthesizing 30 peer-reviewed studies from reputable journals. The findings reveal that the integration of technologies such as learning management systems, wearable trackers, virtual reality, mobile applications, and innovative teaching models (e.g., flipped classroom and gamification) consistently enhances students’ motivation, engagement, and instructional effectiveness in physical education. Nevertheless, challenges remain, including limited infrastructure, teachers’ digital competency gaps, and ethical issues concerning data privacy. The study concludes that the successful implementation of digital technologies in physical education depends on human resource readiness, supportive educational policies, and strengthened digital literacy. It recommends the integration of technology-based curricula and continuous professional development to build an inclusive, secure, and globally competitive digital physical education ecosystem.The digital transformation of physical education has created a new paradigm of learning that is interactive, adaptive, and data-driven. This study aims to review recent methods and digital platforms applied in sports education by analyzing national and international research published between 2020 and 2025. A descriptive–analytical approach was employed by synthesizing 30 peer-reviewed studies from reputable journals. The findings reveal that the integration of technologies such as learning management systems, wearable trackers, virtual reality, mobile applications, and innovative teaching models (e.g., flipped classroom and gamification) consistently enhances students’ motivation, engagement, and instructional effectiveness in physical education. Nevertheless, challenges remain, including limited infrastructure, teachers’ digital competency gaps, and ethical issues concerning data privacy. The study concludes that the successful implementation of digital technologies in physical education depends on human resource readiness, supportive educational policies, and strengthened digital literacy. It recommends the integration of technology-based curricula and continuous professional development to build an inclusive, secure, and globally competitive digital physical education ecosystem.